Meningococcal meningitis in two patients with primary antibody deficiency treated with replacement intravenous immunoglobulin. Issue 11 (27th October 2006) - Lear, S; Eren, E; Findlow, J; Borrow, R; Webster, D; Jolles, S
Abstract : The current treatment of primary antibody deficiency (PAD) is the early recognition of the condition and replacement immunoglobulin combined with prompt treatment of infections and complications. The route of administration (intravenous or subcutaneous), dose and frequency of administration of immunoglobulin still vary between centres and countries. Most infections in patients with PAD are reduced but not entirely prevented by replacement immunoglobulin, with sinopulmonary infections accounting for the bulk of the remainder. Although there have been reports of meningitis in patients with PAD before replacement treatment, we describe the first two cases of bacterial meningitis (group B Neisseria meningitidis ) on adequate immunoglobulin replacement and discuss the involvement of potential cofactors.